Effects of technological change and automation on industry structure and (wage-)inequality: insights from a dynamic task-based model - Herbert Dawid; Michael Neugart (Journal of Evolutionary Economics, 2022)
The advent of artificial intelligence is changing the task allocation of workers and machines in firms' production processes with potentially wide ranging effects on workers and firms. We develop an agent-based simulation framework to investigate the consequences of different types of automation for industry output, the wage distribution, the labor share, and industry dynamics. It is shown how the competitiveness of markets, in particular barriers to entry, changes the effects that automation has on various outcome variables, and to which extent heterogeneous workers with distinct general skill endowments and heterogeneous firms featuring distinct wage offer rules affect the channels via which automation changes market outcomes.
Keywords: C63; L10; J31; O33; 330; Automation; Artificial intelligence; Tasks; Wage inequality; Firm dynamics